Institutional constraints to political budget cycles in the enlarged EU - Esther Ademmer; Ferdinand Dreher (Kiel Institute for the World Economy (IfW), 2014)
This paper revisits Political Budget Cycles (PBCs) in the enlarged European Union (EU). Based on a panel of 25 current EU member states from 1996 to 2012, we show that governments frequently fiscally stimulate the economy prior to elections; a phenomenon that is seemingly not only an 'Eastern problem' of the EU's new members, as has been suggested in the literature. We argue that fiscal institutions are apt to reduce the extent of opportunistic fiscal behaviour both in these younger democracies as well as in other EU member states that lack a strong press to hold governments accountable. Yet, we conclude that in order to eradicate PBCs in the enlarged EU, a powerful press remains key.
Keywords: 330; Central and Eastern Europe; Enlargement; Fiscal Institutions; Political Budget Cycles; Press Freedom